IMMUNOREACTIVITY DISORDER IN CHRONIC HEART FAILURE OF VARIOUS ETIOLOGIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Chronic heart failure (CHF) is a complex clinical syndrome. CHF is the outcome of many cardiovascular diseases, both inflammatory and non-inflammatory in nature, and in most cases leads to permanent disability of patients. Statistics show that over the past 20 years, the prevalence of CHF in developed countries has increased significantly, reaching epidemic levels in some of them, more than 5 million people suffer from heart failure in the United States, 1.5 million of them have its high (III-IV) functional class according to the NYHA classification. Epidemiological data of recent years have revealed such an alarming fact that decompensation of CHF caused hospitalizations to hospitals with cardiology departments in almost every second patient (49%), and CHF appeared in the diagnosis in 92% of patients hospitalized in such hospitals.